2016
DOI: 10.1103/physrevapplied.6.064031
|View full text |Cite
|
Sign up to set email alerts
|

Ultrananocrystalline Diamond Membranes for Detection of High-Mass Proteins

Abstract: Mechanical resonators realized on the nanoscale by now offer applications in mass sensing of bio-molecules with extraordinary sensitivity. The general idea is that perfect mechanical mass sensors should be of extremely small size to achieve zepto-or yocto-gram sensitivity in weighing single molecules similar to a classical scale. However, the small effective size and long response time for weighing biomolecules with a cantilever restricts their usefulness as a high-throughput method. Commercial mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…We deduce for pristine diamond nanomembranes a FE threshold voltage of 1170 V from the I-V curve (Fig. 2(a) blue curve) which is in good agreement with the literature 24 .
Figure 2( a ) Measured current as a function of the applied voltage (I-V) for a pristine diamond membrane and after 3, 6, and 9 cycles of ZnO ALD coating. The data has been smoothen by a simple moving average (n = 10) to guide the eyes.
…”
Section: Resultssupporting
confidence: 88%
“…We deduce for pristine diamond nanomembranes a FE threshold voltage of 1170 V from the I-V curve (Fig. 2(a) blue curve) which is in good agreement with the literature 24 .
Figure 2( a ) Measured current as a function of the applied voltage (I-V) for a pristine diamond membrane and after 3, 6, and 9 cycles of ZnO ALD coating. The data has been smoothen by a simple moving average (n = 10) to guide the eyes.
…”
Section: Resultssupporting
confidence: 88%
“…A drawback to the approach was the small active area as the nanomembranes were approximately 200‐times smaller than MCPs. Recently, Kim et al (2016) demonstrated improved sensitivity, mass resolving power, and faster response times with ultrananocrystalline nanomembranes fabricated using conventional semiconductor etching processes. Mass spectra for two test proteins, insulin and cytochrome c , are shown in Figure 18.…”
Section: Detectors In Dofmsmentioning
confidence: 99%
“…(Right panel) Mass spectrum of cytochrome C obtained using an ultrananocrystalline membrane (R FWHM = 438). Adapted from Kim et al (2016), with permission. ©2016 American Physical Society.…”
Section: Detectors In Dofmsmentioning
confidence: 99%
“…The resulting variations of the electron current, which is emitted from the nanomembrane by field emission and subsequently amplified by the MCP unit, are used to sense the arrival of incoming analyte ions. [17][18][19][20][21][22] In addition, the implementation of independent conversion dynodes in front of the actual MCP proved to be particularly suitable. The analyte ions hit the conversion dynode, resulting in the generation of smaller secondary ions.…”
Section: Introductionmentioning
confidence: 99%